Gilda Joyce : the dead drop - Allison, Jennifer (Dutton Children's Books, 2009)
Gilda Joyce, a teenage psychic investigator, gets to spend the summer interning for the International Spy Museum in Washington, D.C., where she stumbles onto a national security mystery.